Enterprise instant messaging impacts in human factor: application in a consulting services company in information technology - Laureano, Raul M. S.; Santos; Hugo; Gomes, João P. F. (Sistemas y Tecnologías da Información: actas de la 9ª Conferência Ibérica de Sistemas y Tecnologías da Información, 2014)
After a massive adoption by domestic users, instant messaging (IM) wins a significant dimension in business domain. Its adoption in organizations, as a tool in the daily work, leads to a set of changes for all the employees. Their use generates relevant positive impacts, by establishing a more dynamic communication within the organization, but also with clients, partners and suppliers, which results in increased efficiency and productivity. Nevertheless, when mostly used for social chats, rather than professional purposes, or when there are frequent interruptions to their use, the impacts became negative. In order to reveal the perception of the user on using IM, and to evaluate its impact on the human factor, we have outlined this study, which was conducted in a multinational consulting corporation - information technology. It is therefore a case study with a quantitative approach, which was attended by 117 employees. The data was collected from 1-20 July 2013 through a survey. The results show a massive adoption of IM and a tendency to be used by employees who are not displaced, evidencing frequent use on a professional basis. The impacts of the IM adoption are consistent with the policy of human resource management department of the company.